2020
DOI: 10.1007/s00068-020-01449-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of melatonin on reduction in the need for sedative agents and duration of mechanical ventilation in traumatic intracranial hemorrhage patients: a randomized controlled trial

Abstract: Purpose This study aimed to determine the effect of exogenous melatonin on the number of sedative drugs and the duration of mechanical ventilation in traumatic intracranial hemorrhage patients in ICU. Methods This double-blind randomized clinical trial study was conducted in the ICU wards of Golestan Hospital, Ahvaz, Iran, from September 2017 to March 2018. In this study, 52 patients with intracerebral hemorrhage were selected by convenient sampling (26 patients in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Doses have ranged up to 30 mg 16 . Sleep was assessed by questionnaires and indirect objective measures of sleep 16–22 . Sleep quality and patient‐related outcomes, such as length of stay and the amount of administered sedatives, seemed to improve in patients treated with melatonin 16–23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Doses have ranged up to 30 mg 16 . Sleep was assessed by questionnaires and indirect objective measures of sleep 16–22 . Sleep quality and patient‐related outcomes, such as length of stay and the amount of administered sedatives, seemed to improve in patients treated with melatonin 16–23 .…”
Section: Discussionmentioning
confidence: 99%
“…Doses have ranged up to 30 mg. 16 Sleep was assessed by questionnaires and indirect objective measures of sleep. [16][17][18][19][20][21][22] Sleep quality and patient-related outcomes, such as length of stay and the amount of administered sedatives, seemed to improve in patients treated with melatonin. [16][17][18][19][20][21][22][23] A recent Cochrane review evaluated the literature concerning melatonin therapy in the ICU.…”
Section: Melatonin and Sleep In The Icumentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that melatonin reduced the sedative use and the duration of mechanical ventilation for patients with intracerebral hemorrhage in the ICU [108]. The results indicated that the mechanical ventilation time and cumulative doses of morphine were significantly lower in the group treated with melatonin [108]. Hyposecretion of melatonin during mechanical ventilation and disturbed diurnal rhythm has been observed in most patients treated in the ICU [109].…”
Section: Effect Of Melatonin On the Respiratory Systemmentioning
confidence: 99%
“…Several studies implicate endogenous melatonin in the physiological regulation of the circadian mechanisms ruling sleep propensity (33). Melatonin reduces the need for sedation in ICU patients (34)(35)(36)(37)(38)(39). Thus, in the context of COVID-19 pandemic the therapeutical utility of melatonin emerges.…”
Section: Melatonin and Sleepmentioning
confidence: 99%